2003
DOI: 10.1007/s00425-002-0898-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationships between induced jasmonic acid levels and volatile emission in Zea mays during Spodoptera exigua herbivory

Abstract: Jasmonic acid (JA) has long been hypothesized to be an important regulator of insect-induced volatile emission; however, current models are based primarily on circumstantial evidence derived from pharmacological studies. Using beet armyworm caterpillars (BAW: Spodoptera exigua) and intact corn seedlings, we examine this hypothesis by measuring both the time-course of insect-induced JA levels and the relationships between endogenous JA levels, ethylene, indole and sesquiterpenes. In separate Morning and Evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(109 citation statements)
references
References 46 publications
(42 reference statements)
3
102
1
1
Order By: Relevance
“…As thrips infestation activates JA signaling in tomato, we hypothesize that higher thrips feeding damage might have induced increased production of this phytohormone and, consequently, also the production of type-VI trichomes and their associated volatiles. For instance, a direct positive relationship between endogenous JA levels and both sesquiterpene and indole volatile emission has been demonstrated in maize ( Zea mays ) (Schmelz et al 2003). In the same study, Schmelz et al (2003) also showed that JA production was positively correlated with infestation levels of maize plants with S. exigua caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…As thrips infestation activates JA signaling in tomato, we hypothesize that higher thrips feeding damage might have induced increased production of this phytohormone and, consequently, also the production of type-VI trichomes and their associated volatiles. For instance, a direct positive relationship between endogenous JA levels and both sesquiterpene and indole volatile emission has been demonstrated in maize ( Zea mays ) (Schmelz et al 2003). In the same study, Schmelz et al (2003) also showed that JA production was positively correlated with infestation levels of maize plants with S. exigua caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing olfactory cues for neighboring plants, as discussed above, herbivore-induced changes in plant volatile emissions are thought to confer defensive benefits by providing cues that recruit natural enemies of feeding herbivores [24-29] or deter feeding or oviposition by additional herbivores [30-33]. Furthermore, volatile induction is known to be mediated by JA [34,35] and thus is likely to reflect downstream influences of the JA induction we documented previously. In addition to examining the effects of the E. solidaginis emission on S. altissima volatile responses, we conducted parallel experiments in maize ( Z. mays ).…”
Section: Introductionmentioning
confidence: 94%
“…Analysis of phytohormone production and defense gene expression in response to elicitors such as flagellin, elongation factor-Tu (EF-Tu), and chitin, for which the cognate PRRs have been identified, indicate that these conserved bacterial and fungal patterns activate multiple branches of induced immunity, including JATI (Kim et al 2014). Several HAMPs, including fatty acid-amino acid conjugates (FACs), also amplify JA responses via unknown mechanisms (McCloud and Baldwin 1997; Schmelz et al 2003, 2007). Elicitation of JA-mediated defense responses by DAMPs, including the 18-amino-acid peptide systemin and cell wall-derived oligogalacturonides (OGs), is consistent with the ability of these compounds to stimulate endogenous JA synthesis (Doares et al 1995; Lee and Howe 2003).…”
Section: Activation Of the Core Ja Modulementioning
confidence: 99%